Madurese Language Speech Levels and Affixes Analysis of Madurese Folktales Told by Hasan Sasra - Alim, Wahab Syakhirul; Muslifah, Muslifah; Ellizah, Corina; Hasbiy, Khoirul Umam (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
In Indonesia, each ethnic group has its local languages to communicate with one another. The Madurese language stands out among the numerous local languages spoken by diverse ethnic groups in Indonesia due to its uniqueness. Affixes analysis uses in this research to identify how the words form in Madurese Folktales conversations told by Muhammad Hasan Sasra, they are Pa’ Sakèra, Bhindhârâ Sa`ot, Kè Moko, Bhângsa Cara, Raghâ Padmi, Arè’ Madhurâ, Sombhâr Aèng Mata, Makamma Sayid Maulana Yusuf, Perrèng Sojjhinna Kè Rabâ, and Kè Lèsap. The objectives of this research are (1) describing the many speech levels of the Madurese language, specifically in Madurese Folktales. (2) identifying the form and the dominant of the affixation used in Madurese Folktale's conversations. The kind of this research is qualitative descriptive; the objects of this study are nine Madurese Folktales. The method used was library research and observation. The result of this study shows that there are three speech levels throughout the Madurese language, which are Énjé’ Iyéh, Énggê Éntén, and Enggi Buntén. While the affixation analysis, it was found 13 prefixes (a-, n-, pa-, ka-, m-, è-, ny-, ng-, sa-, ka-, ta-, p-, and k-) and 12 suffixes (–ân, -an, -na, -a, -eng/-na, -nga, -è, -aghi, -i, -â, -e, and –èpon/-na). The three dominants of the affixation are a- , è- , and ny- of a prefix, and for suffixes are –na, -a, and –an.